Flow-Diverter Stents for the Treatment of Saccular Middle Cerebral Artery Bifurcation Aneurysms - Caroff, J. (AJNR Am J Neuroradiol, 2016)
BACKGROUND AND PURPOSE: The flow-diverter stent has been proved a feasible, safe, and efficient technique, particularly for the treatment of large and broad-neck carotid siphon aneurysms. Wide-neck bifurcation aneurysms remain, in some cases, a challenge for neurointerventionalists. We report the outcomes of the treatment of saccular middle cerebral artery bifurcation aneurysms with flow diversion in our institution. MATERIALS AND METHODS: From the institution data base, all saccular, nondissecting MCA bifurcation aneurysms, treated with flow-diverter stents, were retrospectively reviewed. Technical issues, immediate posttreatment and follow-up angiographic findings, and clinical outcomes were assessed. RESULTS: Fourteen patients with 15 aneurysms were included in the study. Ischemic complications, as confirmed by MR imaging, occurred in 6 patients (43%). Procedure-related morbidity and mortality at last follow-up were 21% and 0%, respectively. Angiographic follow-up was available for 13 aneurysms, with a mean follow-up of 16 months. Complete occlusion was obtained for 8 aneurysms (62%). CONCLUSIONS: Compared with other available therapeutic options, the flow-diverter stent does not appear to be a suitable solution for the treatment of saccular MCA bifurcation aneurysms.